Nitrate-rich beetroot juice supplementation enhances short but not longer duration running time-trial performance in trained males (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
This study evaluated the effects of nitrate-rich beetroot juice supplementation on exercise performance in trained males conducting short and longer duration self-paced treadmill running time-trials (TT). Eight male runners or triathletes (age: 28.3 +/- 5.8 years, body mass: 74.7 +/- 10.1 kg, height: 179.1 +/- 2.4 cm, V.O2max: 62.3 +/- 8.1 ml g-1 min-1) completed four exercise performance te in a randomised order, comprising 10 minutes of moderate-intensity exercise followed by either a 1500 m or 10,000 m treadmill TT. Participants were supplemented double-blind with either 140 ml concentrated nitrate-rich (BRJ; 12.5 mmol nitrate) or nitrate-deplete placebo (PLA; ~ 0.01 mmol nitrate) beetroot juice, 3 hours before the start of exercise. Pre-exercise plasma nitrite concentrations were significantly elevated in BRJ compared with PLA prior to both the 1500 m (661.3 +/- 263.0 vs. 114.8 +/- 15.8 nM; p = 0.001) and 10,000 m (500.5 +/- 210.5 vs. 102.8 +/- 16.1 nM; p = 0.002) TTs. The increase in plasma nitrite concentrations in BRJ compared with PLA was not significantly different between 1500 m and 10,000 m TTs (p > 0.05). Post-exercise plasma nitrite concentrations significantly decreased in the BRJ 1500 m condition compared to pre-exercise levels (delta 272.0 +/- 229.4 nM; p = 0.01), but did not change relative to pre-exercise levels in all other conditions (all p > 0.05). Post-exercise blood lactate concentrations were significantly greater in BRJ compared with PLA following the 1500 m TT 6.6 +/- 1.2 vs. 6.1 +/- 1.5 mM; p = 0.02), but not significantly different between conditions following the 10,000 m TT (p = 0.96). Resting blood pressure and exercise V.O2 were not significantly different between BRJ and PLA (all p > 0.05). Performance in the 1500 m TT was significantly faster in BRJ versus PLA (319.6 +/- 36.2 vs. 325.7 +/- 38.8 s; p = 0.03). Magnitude based inferences indicated a very likely beneficial effect of BRJ on 1500 m TT performance. Conversely, there was no significant difference in 10,000 m TT performance between conditions (2643.1 +/- 324.1 vs. 2649.9 +/- 319.8 s; p = 0.77). Magnitude based inferences indicated an unclear effect of BRJ on 10,000 m TT performance. These data suggest that BRJ may be ergogenic in trained males conducting short but not longer duration exercise tests.